Localization and posttranslational modifications of otefin, a protein required for vesicle attachment to chromatin, during Drosophila melanogaster development. - Ashery-Padan, R (1997)
Otefin is a peripheral protein of the inner nuclear membrane in Drosophila melanogaster. Here we show that during nuclear assembly in vitro, it is required for the attachment of membrane vesicles to chromatin. With the exception of sperm cells, otefin colocalizes with lamin Dm0 derivatives in situ and presumably in vivo and is present in all somatic cells examined during the different stages of Drosophila development. In the egg chamber, otefin accumulates in the cytoplasm, in the nuclear periphery, and within the nucleoplasm of the oocyte, in a pattern similar to that of lamin Dm0 derivatives. There is a relatively large nonnuclear pool of otefin present from stages 6 to 7 of egg chamber maturation through 6 to 8 h of embryonic development at 25 degrees C. In this pool, otefin is peripherally associated with a fraction containing the membrane vesicles. This association is biochemically different from the association of otefin with the nuclear envelope. Otefin is a phosphoprotein in vivo and is a substrate for in vitro phosphorylation by cdc2 kinase and cyclic AMP-dependent protein kinase. A major site for cdc2 kinase phosphorylation in vitro was mapped to serine 36 of otefin. Together, our data suggest an essential role for otefin in the assembly of the Drosophila nuclear envelope.